(untitled) (Asean Journal of Engineering Education, 2023)
In this innovation, team projects from two courses offered in different semesters are integrated. On top of that, students are trained to use a spreadsheet-based tool to solve the problem in the project. Those two courses are Mass Balance (SETK 1123) and Energy Balance (SETK 2133) offered to Chemical Engineering students in Universiti Teknologi Malaysia at their second and third semester. The main objective of the innovation is to scaffold the students’ understanding of the problems given to them in the projects. At the end of the project, they should be able to clearly see the overall processes in a typical chemical industry, starting from raw materials to the targeted products, by-products, and wastes produced. In addition to that, the projects also foster digital skills by enhancing the students’ skills to use the spreadsheet tools to solve Chemical Engineering problems. This is inline with their study as the students learnt about computer programming and spreadsheet tools in their first semester. From the students’ reflections, it can be concluded that this innovation are able to increase the comprehension of the students on the two courses, increase the skills in using spreadsheet tools for solving problems and also inculcate critical thinking and problem solving skills.